1992
DOI: 10.1063/1.1142538
|View full text |Cite
|
Sign up to set email alerts
|

Hyper-Rayleigh scattering in solution

Abstract: The experimental setup for the implementation of a new technique to determine the hyperpolarizability of nonlinear optical molecules in solution is presented. The new technique, hyper-Rayleigh scattering in solution [K. Clays and A. Persoons, Phys. Rev. Lett. 66, 2980 (1991)], has the advantage over the electric-field-induced second-harmonic generation technique that the dipole moment μ and the second hyperpolarizability γ do not have to be independently determined to obtain the first hyperpolarizability β. No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
313
0
7

Year Published

1996
1996
2002
2002

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 513 publications
(326 citation statements)
references
References 10 publications
6
313
0
7
Order By: Relevance
“…A small portion of the incident beam was directed through a doubling crystal and onto a fast photodiode; this signal was collected simultaneously with the scattering to account for fluctuations in laser power and modelocking stability during the experiments. HRS experiments at 1064 nm were performed using a Nd:YAG laser operating at 10 Hz (300 ps, 40 mJ pulses) and a detection setup similar to that described by Clays and Persoons [3]. Gated electronics and boxcar integration were used to ensure detection of the HRS signal resulting from every pulse.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A small portion of the incident beam was directed through a doubling crystal and onto a fast photodiode; this signal was collected simultaneously with the scattering to account for fluctuations in laser power and modelocking stability during the experiments. HRS experiments at 1064 nm were performed using a Nd:YAG laser operating at 10 Hz (300 ps, 40 mJ pulses) and a detection setup similar to that described by Clays and Persoons [3]. Gated electronics and boxcar integration were used to ensure detection of the HRS signal resulting from every pulse.…”
Section: Methodsmentioning
confidence: 99%
“…In isotropic media, conventional coherent SHG is forbidden in the electric dipole approximation [2]. HRS works, despite the orientational randomization, because signals scale as the variance of the orientation of the species in solution with respect to the incident radiation field [3]. Furthermore, HRS provides advantages over the more standard technique for measuring b, electric field-induced second harmonic generation (EFISHG).…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] However, as far as we are aware, the precise balance between coherent and incoherent HRS has never been estimated for any substance. In order to fill this gap, we have taken up this task for liquid nitrobenzene.…”
Section: 2mentioning
confidence: 99%
“…͑1͒ of this paper͔. In recent years it has become apparent that measurement of HRS in liquids may be used to quantify the nonlinearity in the molecular response: Clays and Persoons 3,4 have shown that measurement of HRS signals allows extracting reliable values for the largest element of the molecular first hyperpolarizability tensor ␤ i jk ͓with i, j,k͕x,y,z͖, and (x,y,z) denoting the molecular coordinate frame͔. Furthermore, subsequent experimental 5 and theoretical 6 work has indicated that the HRS-technique may also be used to determine the values of the other elements of the molecular ␤ i jk tensor, essentially by measuring HRS-depolarization ratios in a series of experiments utilizing both linearly and circularly polarized light.…”
Section: Introductionmentioning
confidence: 99%
“…We use an external reference method, i.e. comparing the slope of a plot of 12~o/I 2 versus N s for the sample with that for a reference molecule: para-nitroaniline (PNA) with /3333 = 23 × 10 -30 esu in chloroform [13,14] (all measurements are performed with chloroform as solvent). This approach effectively eliminates the need for the knowledge (or estimation) of the local field factors since these factors are divided out by measuring in nearly the same local field.…”
Section: Theorymentioning
confidence: 99%